Ciprofloxacin and levofloxacin adversely affect male infertility indicated by pharmacological, andrological and pathological evidence - Mokhimar, Haitham M.; Kandiel, Mohamed M.; Amin, Aziza A.; Elsawah, Hozaifa K.; El Mahmoudy, AbuBakr M. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Drug-induced reproductive organs toxicities is an important aetiology in investigation of male infertility. The aim is to study levofloxacin effect on male reproductive system in comparison to ciprofloxacin. Methods: Twenty-five male wister rats weighted 230±20 gm and aged 8 weeks were randomly divided into five groups of five. The first group received ciprofloxacin with dose 78.23 mg/kg/day in 2 doses (therapeutic dose). The second group received the double dose of the first group ciprofloxacin. The third group received levofloxacin with dose 39.11 mg/kg/day once daily (OD) (therapeutic dose). The Fourth group received the double dose of the third group levofloxacin. However, the fifth group served as a control and received normal saline with carboxymethylcellulose OD. All treatments were administered orally for 14 days. On the 15th day, blood samples and reproductive organs were obtained from all rats. Testicular tissues were prepared for genetic testing and chemical and microscopical examination. Results: Ciprofloxacin and levofloxacin negatively altered reproductive organ weights, sperm parameters and serum follicle stimulating hormone (FSH) and luteinizing hormone (LH) level (p<0.05). Additionally, serum testosterone level was significantly deceased in ciprofloxacin-treated group (the double dose) (p<0.05) relative to control. The difference between ciprofloxacin and levofloxacin was significant in seminal vesicle weight and serum LH and FSH level (p<0.05). Testicular histopathological changes were also found with the two drugs with different degrees. Effects of levofloxacin and ciprofloxacin were dose-dependent. Conclusions: Both ciprofloxacin and levofloxacin adversely affect andrological function that should be monitored and controlled during application of these drugs.